Pengembangan Mobile Learning Menggunakan Adobe Flash Pada Pelajaran Narrative Text Di Smp eLKISI Mojokerto - Ardhian Zahroni (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2019)
English is an important thing to learn by students, because English is an international language. However, English learning in nine grade of eLKISI Junior High School has not been optimally. There are several obstacles that cause learning English to be less than optimal. Such as lack students motivation, limited learning hours, and inexperienced teachers. To solve these problems it is necessary to make product of learning media in the form of android-based applications. Android-based applications are commonly used so that Android-based applications will be easy to use by people. The product contains English narrative text lessons for class IX in Junior High School. Development uses Adobe Flash CS6 software to produce interesting learning media equipped with animation, images and sound. This research and development use the ADDIE development design model. Development products are reviewed by material experts, instructional media experts and learning designs, and tested by students (small groups and large groups), as well as field trials (tryout). The use of applications is done with a variety of places, it can be concluded that the use of applications can be done at any moment. In terms of ease of use of the application, all respondents answered that there were no difficulties.